INDONESIAN PARENTS’ CONSIDERATION TO SELECT CHILDREN BOOKS IN CONSTRUCTING MORAL IDENTITY - Mehrunnisa Ani Mufti (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2022)
Parents believe that books are the media to enhance children’s knowledge enrichment, language development, and linguistic competencies. However, there are limited studies that envisage the involvement of parents in selecting books for their children.  Current research that considers parents’ background as one of the literacy resources remains rare. This narrative inquiry explores Indonesian parents’ consideration in selecting children’s books as a means of constructing moral identity. Parents of a second-grade elementary student in Yogyakarta were the participants in this research. A semi-structured online interview sparked a discussion on what factors they consider when choosing children's books and why. The responses of parents revealed some key concerns about book choices: their experience, child’s contextual needs, and child’s interests. Furthermore, it is found that Indonesian children’s books tend to have moral fallacies that did not fit well with parents’ moral identity. As a result, parents’ book selection for the child was more into foreign publishers because they had more precise Islamic moral value representation.